Indian Agriculture and Rural Economy in Terms of the COVID-19 Pandemic - Michał Mrozek (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of the paper is the analysis of the changes in Indian agriculture during the pandemic. The following research questions were put forward: What is the diversification of the Indian agriculture and rural economy in terms of COVID-19?; What is the percentage change in overall agricultural commodities production, in farm-gate prices for commodities in agriculture and the allied sector and in the availability of agri-inputs? The theoretical part of the paper depicted the following issues: India’s role in global farming; rural economy issues, economic recovery, and the agricultural sector in terms of the COVID-19 pandemic. The studies that were conducted include: documentation, statistical, comparative, and dynamics analysis. The results showed that the Indian agriculture and rural economy in terms of COVID-19 had different tendencies. With businesses across all industries forced to shut down, the economy ground to a halt. Even while farming operations were spared during the lockdown’s early stages, the agricultural value chain nonetheless experienced widespread disruptions. This was devastating to the rural Indian economy.